Improving Students Metacognitive Abilities Through Mind Mapping with Problem based Learning Learning Models on the Concept of Environmental Pollution at SMAN 7 Pekanbaru - Mulyani, Rika; Wulandari, Sri; Mahadi, Imam (Journal of Educational Sciences, 2020)
The K13 Curriculum requires students thinking skills, especially in the regulation of cognition which consists of planning, information management strategies, monitoring, examination of actions, and evaluation. This study aims to look at the metacognitive abilities of class X students of SMAN 7 Pekanbaru on the concept of environmental pollution through mind mapping with problem based learning models. This type of research was a quasi experiment using two classes, one class as an experimental class and one class as a control class. The experimental class used mind mapping models of problem based learning and the control class used conventional learning. The research design used a pretest-posttest control group design. Data collection techniques used questionnaires metacognitive abilities and description test questions. The analysis technique used the Anova test analysis. The results of the pretest and posttest showed a significant increase in students metacognitive abilities through mind mapping with the problem based learning model of the concept of environmental pollution at SMAN 7 Pekanbaru with a significance value of 0,000. Sig. (0,000) < then H0 is rejected, so it can be concluded that the metacognitive abilities of students are increased through mind mapping with problem based learning models on the concept of environmental pollution.